Estudio de factibilidad y diseño de una red Gpon en la ciudad de Loja para la empresa Necusoft Cia.Ltda. Nettplus. - Vélez Vásquez, Cristian Gabriel (2015)
This project proposes a solution to the telecommunications network of Nettplus Company in Loja City, giving a way to new technologies, implementing a next-generation access network based on GPON standard. For the development of the project, it was divided into different sections in order to accomplish an effective investigation and make the best design according to the company requirements. The description about fiber optical networks was made, analyzing the main characteristics of optical networking systems. Besides, the main troubles that affect the optical fiber; types; applications; advantages and disadvantages. The major existing GPON network architectures and the study of standard passive GPON optical access networks was also analyzed. After that, the study and information gathering for the network design was performed, the solutions presented in the standard terms of its architecture. Topology: indicating its active elements and passive elements for implementing a GPON network. Finally, the obtained results are described after the analysis of different possible solutions. Comparing advantages and disadvantages of each one, the following step was selecting the best network model which allows access to a network with a high standards of efficiency, flexibility and availability and to be useful now and in the future. The required equipment was selected to provide a complete solution for the design, and the real cost for make this design possible.